Prevalensi Hepatitis C ada Pendonor Darah Di UTD PMI Kabupaten Bantul Tahun 2019-2020 - Shinta (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Hepatitis C is a disease that often causes swelling of the liver and can cause complications. Hepatitis C is the second problem in the world after Hepatitis B. Indonesia ranks third in the world for the most hepatitis sufferers, with an estimated 30 million people suffering from hepatitis B and hepatitis. C. Hepatitis C can be spread through blood transfusions from donors with reactive hepatitis C. In UTD PMI Bantul Regency, there are still cases of Hepatitis C infection in donors in 2019-2020. Therefore, this study aims to determine the prevalence of Hepatitis C in 2019-2020. The research method used is descriptive research with a quantitative approach with a total sampling technique. The population in this study is all data on blood donors at UTD PMI Bantul Regency in 2019-2020 with a total of 16,727. The samples used were blood donors with reactive Hepatitis C from 2019 to 2020 as many as 26 donors. Laboratory examination in the form of hepatitis C screening was carried out using the CLIA (Chemiluminescence Immunoassay) method. From the results of this study, it was found that the prevalence of Hepatitis C in blood donors in UTD PMI Bantul Regency in 2019-2020 was 0.15%. The prevalence in 2019 was 12 (0.14%) and in 2020 it was 14 (0.16%). ). The percentage of Hepatitis C in male blood donors is higher than in women. In 2019 it was 11 (91.66%) and in 2020 it was 11 (78.6%). The highest prevalence of Hepatitis C in blood donors is at the age of 24-44 years. in 2019 it was 8 (66.7%) and in 2020 it was 12 (85.7%).